A Descriptive Study of the Daily Dietary Patterns of Stunted Children - Zauhani Kusnul; Yuly Peristiowati; Herin Mawarti; Dina Dewi Sartika L Ismail; Wiwik Afridah; Duwi Basuki; Wahyu Sri Astutik; Aesthetica Islamy; Janes Jainurrakhma (Journal Of Nursing Practice, 2026)
Background: Toddler age is a period of very rapid growth and development. At this time, it is important to meet the need for adequate nutritional intake in terms of quantity and quality. Malnutrition is a condition where toddlers experience nutritional deficiencies due to low energy and protein intake over a long period of time. Nutritional problems at an early age not only have an impact on impaired growth and development of children, but also increase toddler mortality rates, reduce intelligence levels, increase the risk of mental retardation, and reduce work performance and productivity. Purpose: The purpose of this study was to obtain detailed information about the daily eating patterns of stunted children. Methods: The population of this research was stunted toddlers base in the area of Publich health services of Bendo, Pare. From the all posyandu we chooce one posyandu ada the target by randomize methods. Then we find Dahlia Posyandu as the sample. Posyandu Dahlia has five stunted toddlers so we take them as our sample. Data was taken using a food recall form filled out by the toddler's mother for one week. Furthermore, the data was processed descriptively and presented in the form of a distribution table. Results: This study shows that all toddlers eat three main meals a day, in terms of daily vegetable and fruit consumption, the majority of children rarely eat vegetables and sufficient daily calorie intake, even more than the Daily Calorie Requirement Standard for fruit, In terms of snack food consumption, all children eat snacks very often and the types of snacks eaten are snacks with a strong savory taste and candy. Conclusion: The problem in the diet of stunted children is not just in the adequacy of calories, but in the diversity of sources of protein, fruit and vegetables.